(untitled) (Research, Society and Development, 2021)
Harvesting constitutes one of the main stages within the bean production process, since it has a high aggregate cost and if carried out in the wrong way can cause significant losses. The objective of this work was to evaluate the quantitative losses in the mechanized harvest of beans under different speeds of the harvester and moisture content of the grains. The experiment was conducted from July to November 2019. The design used was completely randomized in a 3x2 factorial scheme, with three harvest speeds (3.5, 4.5 and 5.5 km h-1) and two moisture contents grains (12 and 14%), with six replications. Natural losses, due to cutting defects, in the internal and total mechanisms were measured. The speed factor was not significant in any of the assessed losses, although the average values of total losses obtained for all studied speeds are above the acceptable limit. The moisture content affected the internal and total losses, with the highest results obtained with 14%.